2020
DOI: 10.1186/s13046-020-01705-9
|View full text |Cite
|
Sign up to set email alerts
|

MiR-103a-3p promotes tumour glycolysis in colorectal cancer via hippo/YAP1/HIF1A axis

Abstract: Background Glycolysis plays an essential role in the growth and metastasis of solid cancer and has received increasing attention in recent years. However, the complex regulatory mechanisms of tumour glycolysis remain elusive. This study aimed to explore the molecular effect and mechanism of the noncoding RNA miR-103a-3p on glycolysis in colorectal cancer (CRC). Methods We explored the effects of miR-103a-3p on glycolysis and the biological functions of CRC cells in vitro and in vivo. Furthermore, we investiga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 49 publications
0
38
0
Order By: Relevance
“…The depletion of CRB3 can inhibit the Hippo pathway and lead to increased nuclear localization of YAP [ 30 , 31 , 43 ]. The Hippo pathway plays a crucial role in regulating CRC progression [ 44 47 ]. In the present study, we also observed that CRB3 knockdown inhibited the Hippo pathway and increased the nuclear localization of YAP, suggesting that CRB3 regulates CRC progression through the Hippo pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The depletion of CRB3 can inhibit the Hippo pathway and lead to increased nuclear localization of YAP [ 30 , 31 , 43 ]. The Hippo pathway plays a crucial role in regulating CRC progression [ 44 47 ]. In the present study, we also observed that CRB3 knockdown inhibited the Hippo pathway and increased the nuclear localization of YAP, suggesting that CRB3 regulates CRC progression through the Hippo pathway.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 TEAD1 could directly integrate with the hypoxiainducible factor-1A (HIF-1A) promoter region and regulate the expression of HIF1A, facilitating the tumor glycolysis. 24,25 TEAD2 was significantly upregulated in hepatocellular carcinoma (HCC) and the higher expression was associated with poor OS time of HCC. 26,27 In addition, TEAD3 could promote the proliferation of gastric cancer cell line MKN-28 through increasing SLC35B4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…If the pathway is blocked or inactivated, unphosphorylated YAP/TAZ may enter the nucleus from the cytoplasm, and combine with TEADs to promote gene transcription, induce cell transformation, and enhance the cell proliferation, invasion, and metastasis [ 31 ]. The abnormal regulation of Hippo signaling pathway is associated with the occurrence and development of diverse types of cancer, such as colorectal cancer [ 32 ], gastric cancer [ 33 ], breast cancer [ 34 ], and MPM [ 35 ].…”
Section: Discussionmentioning
confidence: 99%